Analisis Pengaruh Karakteristik Konsumen Dan Faktor Sosial Terhadap Keputusan Pembelian Produk Ramah Lingkungan (Studi Kasus Masyarakat Kota Metro) - Saputra, Dani Septian; Fitriani, Fitriani (Universitas Muhammadiyah Metro, 2023)
The emergence of concern for the environment can change a person in determining which product to choose by considering the impact that will occur on the environment.Therefore, efforts are needed to find out what factors are related to purchasing decisions for environmentally friendly products. This study aims to determine the effect of consumer characteristics and social factors on purchasing decisions of environmentally friendly products in the people of Metro City.The research design is quantitative research or verification research. The method used in this research is the explanatory survey method. The objects in this study are consumer characteristics, social factors and purchasing decisions for environmentally friendly products. This research activity was conducted in Metro City. The research population is consumers in Metro City with a total sample of 96 respondents. Data collection techniques using questionnaires. The analytical tool used isdata quality analysis and multiple linear regression analysis with SPSS program. The results of the study partially show that consumer characteristics and social factors have a significant effect on purchasing decisions for environmentally friendly products. Simultaneously also shows that k consumer characteristics and social factors have a significant effect together on purchasing decisions for environmentally friendly products.Keywords: Consumer Characteristics, Social Factors, Purchase Decision